The Impact of Service Quality on Customer Behavioral Loyalty in the Case of Travel Agencies from Romania - Ovidiu I. Moisescu; Oana A. Gica (Amfiteatru Economic Journal, 2014)
Even though the concept of loyalty has been a key issue in tourism destination marketing for the last decades, the issue of customer loyalty in the case of travel agencies seems to be less emphasized in the specialized literature. The current research is part of a larger study directed at analyzing the impact of corporate social responsibility (CSR) on customer loyalty. Improving service quality is a fundamental part of the social responsibility of tourism businesses, while creating, maintaining and increasing customer loyalty is essential for the sustainability of these businesses. Starting from these assertions, the current paper tries to reveal certain correlations and to identify a model that depicts the impact of travel agencies' service quality on their customers' loyalty. In order to accomplish these goals, an online survey has been conducted among a sample of 286 Romanians which travelled using the services of a travel agency. In order to evaluate service quality, the SERVPERF assessment procedure was adapted to the case of travel agencies, using items related to tangibles (physical facilities, equipment and appearance of personnel), reliability (ability to perform the promised service dependably and accurately), responsiveness (willingness to help customers and provide prompt service), assurance (knowledge and courtesy of employees and their ability to inspire trust and confidence - including competence, courtesy, credibility and security), and empathy (caring and individualized attention that the firm provides to its customers - including access, communication, understanding the customer). In what concerns customer loyalty, the paper focuses on its behavioral facet, namely on the recommendations effectively made regarding certain travel agencies. In the proposed model, the scores regarding perceptions (SERVPERF) were approached as independent variables, while behavioral loyalty was depicted as dependent variable.
Keywords: M31; L83; 330; travel agency; behavioral loyalty; service quality; SERVPERF; CSR; empirical